Effect Cashless Payment on Inflation with Velocity of Money as Intervening Variable - Anggraini, Alifianur; Agustin, Grisvia (Jurnal Ekonomi Balance, 2022)
This study aims to examine the effect of debit cards, credit cards, e-money on inflation and the velocity of money as an intervention. Data in this study were obtained from trusted sources and the official websites of BI and BPS for the 2016-2020 period. The research data is secondary data in the form of time series data. This research uses the method of path analysis or path analysis and the data will be processed using SPSS. Test methods include classical assumption test, hypothesis test and test of the coefficient of determination R^2. The significance level of this study is 5%. The results of this study state that in the first equation directly e-money has no significant effect on the velocity of money but credit cards and debit cards have a significant effect on the velocity of money, in the second equation directly debit cards and e-money have no effect on inflation, while credit cards and the velocity of money have a significant influence on inflation, indirectly the velocity of money is able to be an intervening between credit cards, debit cards, and e-money on inflation